Long‐term outcome of intraventricular conduction delays in the general population - Rankinen, Jani (Ann Noninvasive Electrocardiol, 2020)
BACKGROUND: Previous population studies have presented conflicting results regarding the prognostic impact of intraventricular conduction delays (IVCD). METHODS: We studied long‐term prognostic impact and the association with comorbidities of eight IVCDs in a random sample of 6,299 Finnish subjects (2,857 men and 3,442 women, mean age 52.8, SD 14.9 years) aged 30 or over who participated in the health examination including 12‐lead ECG. For left bundle branch block (LBBB) and non‐specific IVCD (NSIVCD), two different definitions were used. RESULTS: During 16.5 years’ follow‐up, 1,309 of the 6,299 subjects (20.8%) died and of these 655 (10.4%) were cardiovascular (CV) deaths. After controlling for known clinical risk factors, the hazard ratio for CV death, compared with individuals without IVCD, was 1.55 for the Minnesota definition of LBBB (95% confidence interval 1.04–2.31, p = .032) and 1.27 (95% confidence interval 0.80–2.02, p = .308) for the Strauss’ definition of LBBB. Subjects with NSIVCD were associated with twofold to threefold increase in CV mortality depending on the definition. While right bundle branch block, left anterior fascicular block and incomplete bundle branch blocks were associated with seemingly higher mortality, this was no longer the case after adjustment for age and sex. The presence of R‐R’ pattern was not associated with any adverse outcome. CONCLUSIONS: In a population study with long‐term follow‐up, NSIVCD and Minnesota definition of LBBB were independently associated with CV mortality. Other IVCDs had no significant impact on prognosis. The prognostic impact of LBBB and NSIVCD was affected by the definition of the conduction disorder.